Qualitative Methods in Information Research - Steinerová, Jela (Qualitative and Quantitative Methods in Libraries, 2019)
The paper is aimed at review of qualitative methods in information research. Theoretical sources of the qualitative research style are identified, using methodologies applied from psychology, social psychology and phenomenography. Analytical procedures in qualitative methods are explained, namely the content analyses, interpretations, concept mapping. Examples of our qualitative studies of relevance, information ecology and information horizons mapping are mentioned. Findings of a recent qualitative study of information behavior of researchers with respect to research creativity are mentioned in detail. The methodology of semi-structured interviews with 19 selected top researchers in Slovakia was applied. Research creativity is determined and visualized by a conceptual map representing the collective discourse of researchers. Perception of research creativity includes innovations, bird´s-eye view, new ideas, overlaps. Differences in domains are considered (interpretations, problem solving, discovery). Support of creativity as part of ecological information interactions is proposed with the emphasis on methodological creativity. Significance of the qualitative style of research in information science is summarized, namely understanding contexts, human experience, intuition, emotions and development of new methodologies.